Orthodox Christian identity in Western Europe : contesting religious authority - Rimestad, Sebastian (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book analyses the discourses of Orthodox Christianity in Western Europe to demonstrate the emerging discrepancies between the mother churches in the east and their western congregations. Showing the genesis and development of these discourses over the 20th century, it examines the challenges the Orthodox Church is facing in the modern world. Organised along four different discursive fields, the book uses these fields to analyse the Orthodox Church in Westenr Europe during the 20th century. It explores pastoral, ecclesiological, institutional, and ecumenical discourses in order to present a holistic view of how the actors in the church view themselves and how they seek to interact with other denominations. Taken together, the four discursive fields reveal a discursive vitality outside of the traditionally Orthodox societies that is, however, only partly reabsorbed by church hierarchs in core Orthodox regions, like Southeast Europe and Russia. The Orthodox Church is a complex and multifaceted global reality. Therefore, this book is a vital guide to scholars studying the Orthodox Church, ecumenism, and religion in Europe, as well as those working in religious studies, sociology of religion, and theology more generally"--
The Orthodox faithful as 'diaspora'? The pastoral discourse -- The territoriality of Orthodox Church structures : the ecclesiological discourse -- Orthodox jurisdictions as organisations : The institutional discourse -- The Christian Church as one : the ecumenical discourse.
OCLC-licensed vendor bibliographic record.
Keywords: Orthodox Eastern Church -- Europe, Western; Orthodox Eastern Church members -- Europe, Western; Identification (Religion); Group identity -- Europe, Western; Church -- Authority; Europe, Western -- Church history; Europe, Western -- Religion; RELIGION / Christianity / Orthodox Churches; SOCIAL SCIENCE / Sociology of Religion